Purification of the migration stimulating factor produced by fetal and breast cancer patient fibroblasts. - Grey, A M (1989)
We have previously shown that (i) human skin fibroblasts of fetal and adult origin display distinctive migratory phenotypes, (ii) this difference in cell behavior results from the production of a soluble "migration stimulating factor" (MSF) by fetal cells, and (iii) skin fibroblasts from breast cancer patients commonly resemble fetal fibroblasts both in migratory phenotype and in production of MSF. Data are now presented indicating that MSF present in the conditioned medium of fetal and cancer patient fibroblasts is precipitated at 10% saturation ammonium sulfate and binds to heparin and cation-exchange resins. Based on this information, we have devised a scheme for the purification of MSF involving the sequential application of ammonium sulfate precipitation, heparin affinity, gel filtration, and reverse-phase chromatography. Purified MSF has an estimated molecular mass of 70 kDa; amino acid analysis reveals a relatively high level of proline (13.34 residues per 100). Our results further suggest that skin fibroblasts from breast cancer patients produce an additional factor with migration stimulating activity; this factor is precipitated at higher concentrations of ammonium sulfate and binds to anion-exchange resins. We have previously discussed the possible direct involvement of fetal-like fibroblasts in cancer pathogenesis. The availability of MSF obtained from cancer patient fibroblasts provides a potential means with which to examine the complex cellular interactions contributing to this process as well as develop a screening regime for identifying individuals at elevated risk of developing cancer.